Asymmetric Michael addition reactions catalyzed by calix[4]thiourea cyclohexanediamine derivatives - Li, Zheng-Yi; Tong, Hong-Xiao; Chen, Yuan; Su, Hong-Kui; Xiao, Tangxin; Sun, Xiao-Qiang; Wang, Leyong (Beilstein Journal of Organic Chemistry, 2018)
A number of upper rim-functionalized calix[4]thiourea cyclohexanediamine derivatives have been designed, synthesized and used as catalysts for enantioselective Michael addition reactions between nitroolefins and acetylacetone. The optimal catalyst 2 with a mono-thiourea group exhibited good performance in the presence of water/toluene (v/v = 1:2). Under the optimal reaction conditions, high yields of up to 99% and moderate to good enantioselectivities up to 94% ee were achieved. Detailed experiments clearly showed that the upper rim-functionalized hydrophobic calixarene scaffold played an important role in cooperation with the catalytic center to the good reactivities and enantioselectivities.
Keywords: asymmetric Michael addition reaction; calix[4]arene; cyclohexanediamine; thiourea